Handbook of Cardiac Anatomy, Physiology, and Devices - Iaizzo, Paul A. (Springer, 2015)
Personalized medicine, clinical imaging, and the medical device industry continue to grow at an incredibly rapid pace. Further, our overall understanding of the molecular basis of diseases steadily increases, as does the number of available therapies to treat specifi c health problems. This remains particularly true in the fi eld of cardiovascular care. With this rapid growth rate in cardiac medicine, clinicians and biomedical engineers alike have been challenged to either retool or continue to seek out sources of concise information. The major impetus for this third edition was to update this resource textbook for interested students, residents, clinicians, and/or practicing biomedical engineers. A secondary motivation was to promote the expertise, past and present, in the areas of cardiovascular science at the University of Minnesota. As Director of Education for the Lillehei Heart Institute and Associate Director for Education of the Institute for Engineering in Medicine at the University of Minnesota, I feel that this book also represents a unique outreach opportunity to carry on the legacy of Drs. C. Walton Lillehei, M.D., Ph.D., and Earl Bakken, M.D., Ph.D. (Hon.) through the twenty-fi rst century. Interestingly, the completion of this textbook coincides with two recent important anniversaries in cardiovascular medicine and engineering at the University of Minnesota. First, it was 61 years ago, in 1954, that Dr. C. Walton Lillehei performed the fi rst cross-circulation procedures at the University. One year ago in January, Earl Bakken (the cofounder of Medtronic) turned 90 years old; Dr. Bakken has fi ve implanted Medtronic devices and continues to be an inspiration to those working in this fi eld. For the past 15 years, the University of Minnesota has presented the week-long short course Advanced Cardiac Physiology and Anatomy , which was designed specifi cally for the biomedical engineer working in the industry; this serves as the course textbook. Thus there was a need to update the textbook to include state-of-the-art information on a variety of topics related to cardiac anatomy, physiology, and devices. For example, six new chapters were added to this third edition, and all other chapters were carefully updated and/or greatly expanded. One last historical note that I feel is interesting to mention once again is that my current laboratory, where isolated heart studies are performed weekly (the Visible Heart ® laboratory), is the same laboratory in which C. Walton Lillehei and his many esteemed colleagues conducted the majority of their cardiovascular research studies in the late 1950s and early 1960s. It is also the laboratory where Earl Bakken, along with Drs. Vincent Gott and Lillehei, fi rst tested the wearable battery-powered pacemaker on an animal with an induced heart block. After being tested on an animal, the prototype pacemaker was very quickly (later the same day) used by Dr. Lillehei on one of his cardiac surgical patients. With this new edition, complimentary materials (e.g., movies and images) that will enhance this textbook’s utility can be accessed online. Additionally, my laboratory continues to support the online, free access website The Atlas of Human Cardiac Anatomy ( www.vhlab.umn.edu/ atlas ) which also contains many tutorials and unique movie clips of functional cardiac anatomy. These images were obtained from human hearts made available via LifeSource (St. Paul, MN, USA), through the generosity of families and individuals who made the fi nal gift of organ donation for research (their hearts were not deemed viable for transplantation).